Panggung Geografis Peradaban Islam - Munthe, Hasanuddin; Dahlan, Zaini (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
The aim of this research is to find out about the geographical stage of Islamic civilization. The research methodology uses a literature review or library research method with a problem solving approach using analysis. This research attempts to collect research data from the literature and uses literature as the main material for analysis The geographical stage of Islamic civilization explains the location of the Hijaz region in the land of Mecca to Medina to the city of Yemen, where the Hijaz region has both fertile and barren land, so this often causes chaos. Geographically, the Hijaz is a unified country that supports each other and fulfills human needs. . Even though Mecca and Medina are barren countries, the surrounding countries are fertile and prosperous countries. Therefore, this country needs each other. Meanwhile, Yemen has a fertile soil texture and is able to irrigate barren lands. The geographical description of the Hijaz is a picture of Allah's power so that humans do not have pride.